Using Youtube in Make Up Training by Citizens Learned in PKBM Sahabat Kampung Ladang Kecamatan Nan Sabaris District - Mardiyatul Husna; Jamaris Jamna (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
This research is motivated by the high interest and participation of participants in the Make-up training. It is suspected that participants still need Youtube media to support learning outcomes in terms of performance, management of the learning environment, and implementation of learning evaluation. This type of research is quantitative descriptive with a population of 32 participants and a sample of 32 participants using total random sampling technique. The data collection tool used was a questionnaire with percentage calculation data analysis. The research results show the following. First, the implementation of YouTube use and make-up training by learning citizens at PKBM Sahabat, seen from the aspect of preparation, were carried out well. Second, the implementation of the use of YouTube and make-up training by learning citizens at PKBM Sahabat, seen from the implementation aspect, was well implemented. Third, the implementation of the use of YouTube and make-up training by learning citizens at PKBM Sahabat, seen from the aspect of assessment, was carried out well. Researchers suggest that tutors in make-up training at PKBM Sahabat should give awards or rewards to learning citizens who have succeeded well and satisfactorily after the assessment of the make-up training is carried out.Keyword: youtube, make up, training